Cost Implications of Varying the Surgical Setting and Anesthesia Type for De Quervain Release Surgery - Stephens, Andrew R.; Yu, Ziji; Presson, Angela P.; Tyser, Andrew R.; Kazmers, Nikolas H. (Journal of Wrist Surgery, 2020)
Background First extensor compartment release is a common surgical procedure that represents a financial burden to the health care system.Questions/Purposes Study questions included (1) whether surgical encounter costs differ based upon surgical setting (operating room [OR] vs. procedure room [PR]) or (2) based upon anesthesia choice (local only, Bier's block [BB], monitored anesthesia care [MAC], or general [GA]) for De Quervain release (DQR).Patients and Methods Consecutive adult patients undergoing isolated unilateral DQR at a single academic medical center were identified retrospectively by Current Procedural Terminology code (25000). Using our institution's information technology value tools, we calculated total direct costs for each surgical encounter. Costs were adjusted to January 2016 dollars using the Consumer Price Index, normalized using each participant's surgical encounter cost divided by the median cost in the PR group, then compared across each group using Kruskal–Wallis and Nemenyi's post hoc pair-wise tests. Multivariable gamma regression analysis with a log link was performed to identify factors associated with surgical costs. QuickDASH (disabilities of the arm, shoulder, and the hand) scores were compared using a t-test at final follow-up.Results Among 58 included patients, 29% (17/58) were treated in the PR and 71% (41/58) in the OR. Compared with local only in the PR, all other groups were significantly more costly. Multivariable gamma regression indicated that use of OR/BB, OR/MAC, or OR/GA independently led to 211, 222, and 357% greater surgical costs as compared with the PR with local only while controlling for provider and patient age. Furthermore, QuickDASH scores were similar between PR and OR groups at final follow-up.Conclusion Performing DQR in the PR setting under local only anesthesia yields greater value than the OR, as patient-reported outcomes are similar despite significantly lower surgical costs. Level of Evidence This is a Level III, cost analysis study.
Keywords: cost; De Quervain; surgery/surgical; tendinitis; tendinopathy; value